2017
DOI: 10.1039/c7tb00896a
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of hydrogel material composition on hBMSC differentiation into zone-specific neo-cartilage: engineering human articular cartilage-like tissue with spatially varying properties

Abstract: Material composition alone can be used to direct human bone marrow stromal cells into distinct, zone-specific cell phenotypes and spatially-varying, multi-layered material scaffolds can generate complex, patterned tissue structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…13 Parratt et al investigated the effect of hydrogel composition on the human bone marrow stromal cell (hBMSC) differentiation into zone-specific cell phenotypes for the generation of human articular cartilage tissue. 27 This study showed that a composite multilayered material scaffold improved hBMSC differentiation into cartilage-like tissue by increasing sulfated glycosaminoglycans (sGAG) secretion and decreased collagen level. The sGAG is an important component in the cartilage ECM promoting mechanical strength of the scaffold.…”
Section: Recent Advances In Application Of Smart Biomaterialsmentioning
confidence: 96%
See 1 more Smart Citation
“…13 Parratt et al investigated the effect of hydrogel composition on the human bone marrow stromal cell (hBMSC) differentiation into zone-specific cell phenotypes for the generation of human articular cartilage tissue. 27 This study showed that a composite multilayered material scaffold improved hBMSC differentiation into cartilage-like tissue by increasing sulfated glycosaminoglycans (sGAG) secretion and decreased collagen level. The sGAG is an important component in the cartilage ECM promoting mechanical strength of the scaffold.…”
Section: Recent Advances In Application Of Smart Biomaterialsmentioning
confidence: 96%
“…Biodegradable hydrogel systems typically make use of stimuli-specific cleavable cross-linkers, , which can be cleaved through hydrolysis, proteolysis, or disentanglement in response to stimuli . Parratt et al investigated the effect of hydrogel composition on the human bone marrow stromal cell (hBMSC) differentiation into zone-specific cell phenotypes for the generation of human articular cartilage tissue . This study showed that a composite multilayered material scaffold improved hBMSC differentiation into cartilage-like tissue by increasing sulfated glycosaminoglycans (sGAG) secretion and decreased collagen level.…”
Section: Recent Advances In Application Of Smart Biomaterialsmentioning
confidence: 99%
“…The middle-like layer is composed of 10% PEGDA + 10% CSMA in which Col X and sGAG are the highest. [191] HA-based hybrid scaffolds are made with the goal of inducing zonal-specific cellular morphology and ECM composition. Two layers of HA hydrogels enveloping specifically or randomly orientated PLA nanofibers are designed for SZ and MZ, whereas the gel with multiple vertical channels is developed for the DZ.…”
Section: Ecmmentioning
confidence: 99%
“…Many native tissues contain gradients, such as cartilage and the osteochondral gradient between cartilage and bone. 134,135 As a result, biomaterial strategies have been developed to create gradients similar to tissues, including layer-bylayer [136][137][138][139] and 3D printing 140 strategies. Although there are three distinct layers in cartilage (superficial, middle, and deep zones), the challenge is to build many layers on top of one another to seamlessly transition from one zone to the next.…”
Section: Reviewmentioning
confidence: 99%